‘But what hope is there for a nation which lives on potatoes?’: A Brief History of the Statistical and Social Inquiry Society of Ireland - Whelan, Shane (Statistical and Social Inquiry Society of Ireland, 2024)
This paper gives a brief history of the Society. It suggests that what is remarkable about the Society is not its origin but its longevity: it is the sixth longest surviving statistical society in the world at 177 years old when almost all such societies perished in their infancy. The survival and continued relevance of this volunteer organisation is attributed to two factors: council and other active members have the ear of policymakers, often as advisers, and the Society offers the rest of us an opportunity to participate in the debate of evidence-based reforms to help make a better future for those in Ireland.
read before the Society, 30th May 2024
Keywords: Ireland; learned society; statistical society; economic society; reform society; economic policy formation in Ireland; 314.15